A validation of the Nottingham Clavicle Score: a clavicle, acromioclavicular joint and sternoclavicular joint–specific patient-reported outcome measure - Charles, Edmund R.; Kumar, Vinod; Blacknall, James; Edwards, Kimberley L.; Geoghegan, John M.; Manning, Paul A.; Wallace, W. Angus (Elsevier, 2017)
Background